Travels and archaeology in South Chile - Bird, Junius Bouton, 1907-1982 (University of Iowa Press, 1988)
"This is a remarkable book by one of the true geniuses in the field of anthropology during this century and one who provided valuable data for specialists in other disciplines as well."â€"H. M. Wormington"An engaging manuscript that should charm a broad audience."â€"Thomas F. Lynch"The field notes of Junius, and Peggy's diary, are valuable records of the excavations, artifacts, and interpretations of the best archaeologists to work in the southern tip of South America."â€"James G. GriffinJunius Bird's three great archaeological field achievementsâ€"at the Strait of Magellan in Chilean Patagoni.
Keywords: Bird, Junius Bouton, -- 1907-1982.; Bird, Junius B. -- (Junius Bouton), -- 1907-1982.; Bird, Junius Bouton, -- 1907-1982; Indians of South America -- Chile -- Antiquities.; Chile -- Antiquities.; Peuples autochtones -- Chili -- Antiquités.; Chili -- Antiquités.; HISTORY.; SOCIAL SCIENCE -- General.; Antiquities; Indians of South America -- Antiquities; Chile; Reisebericht; Vor- und Frühgeschichte; Ausgrabung; Chile -- Süd; Indiens -- Chili -- Antiquités.; Chile -- Antiquitaes.